2003
DOI: 10.1051/vetres:2003034
|View full text |Cite
|
Sign up to set email alerts
|

The effect of milk production level on host resistance of dairy cows, as assessed by the severity of experimental Escherichia coli mastitis

Abstract: -This study investigated the possible effects of milk production level on the host resistance of dairy cows. High (n = 18) and low (n = 18) producing cows on a research farm, which respectively produced 11 443 and 7 727 kg milk in their previous lactation, were compared. To enhance the possible differences in host resistance between high and low producing cows, the animals in both groups were metabolically stressed by overfeeding during the dry period or were fed according to requirements, resulting in four gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
16
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 21 publications
5
16
0
Order By: Relevance
“…This is confirmed in the literature (Kornalijnslijper et al 2003). The increase in the percentage of CD4 + lymphocytes is associated with a change in the immunological profile towards Th1 cells.…”
Section: Discussionsupporting
confidence: 86%
“…This is confirmed in the literature (Kornalijnslijper et al 2003). The increase in the percentage of CD4 + lymphocytes is associated with a change in the immunological profile towards Th1 cells.…”
Section: Discussionsupporting
confidence: 86%
“…A significant number of studies used experimentally infected udders to study the events after pathogen contact [23,24,31].…”
Section: Introductionmentioning
confidence: 99%
“…The time of the experimental infection differed between 72 h [26] and 48 days [39] for both bacterial species, sometimes with repeated infections of the animals [26]. The infection dose varied for both S. aureus and E. coli between 50 and about 10 000 colony forming units (CFU per udder quarter) [23,55]. In addition, animals were not always prescreened for a prolonged absence of pathogenic bacteria within the udder prior to experimental infections [40].…”
Section: Introductionmentioning
confidence: 99%
“…Mastitis severity has also been shown to vary greatly, even under controlled experimental settings where pathogen factors are held constant. This suggests host factors play a significant role in mastitis outcome [11]. Several studies have shown a dysregulated population of milk and serum neutrophils, along with greater concentrations of TNF-α and reactive oxygen species, during the peri-partum period when animals are highly susceptible to severe mastitis [12].…”
Section: Introductionmentioning
confidence: 99%